6a-2(4a-5)=

Simple and best practice solution for 6a-2(4a-5)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6a-2(4a-5)= equation:


Simplifying
6a + -2(4a + -5) = 0

Reorder the terms:
6a + -2(-5 + 4a) = 0
6a + (-5 * -2 + 4a * -2) = 0
6a + (10 + -8a) = 0

Reorder the terms:
10 + 6a + -8a = 0

Combine like terms: 6a + -8a = -2a
10 + -2a = 0

Solving
10 + -2a = 0

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-10' to each side of the equation.
10 + -10 + -2a = 0 + -10

Combine like terms: 10 + -10 = 0
0 + -2a = 0 + -10
-2a = 0 + -10

Combine like terms: 0 + -10 = -10
-2a = -10

Divide each side by '-2'.
a = 5

Simplifying
a = 5

See similar equations:

| -5t=-c-2 | | 3x-2(2x-6)=2x-9 | | 4x^2-20x+155=0 | | 6+4x=6+4x | | c=5t-2 | | -24+6y=-6 | | 2+5(6n-1)=-63 | | 6x=57.6 | | 4+x+1=8 | | 3.2x=26.6 | | 1.2=y-0.21 | | -5(m-8)=27-7m | | 2a+7-6a= | | 1-21x=-20-9x | | -8+7n+8n^2=0 | | 3(2n+5)=33 | | 2n-5=25 | | -2(8x+2)=-16x+2 | | 2z+5(3z-6)= | | 17-3(2n-5)=30-6n | | X-3(-2)=5 | | Log[4]6-log[4]-2x=1 | | (2X)-13=X+12 | | 7n+3(4n+8)=5 | | 3t-29=32+4t | | 4x+11y=213 | | X+12=(2*x)-13 | | 4.3x=4.3x | | 4y-32=12x | | (5x-1)+(2x+3)= | | 3y-10-15y=-6y+14 | | 4+8r=-4+7r |

Equations solver categories